2008
DOI: 10.1158/1535-7163.mct-08-0024
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of the matrix metalloproteinase–activated anthrax lethal toxin is dependent on gelatinase expression and B-RAF status in human melanoma cells

Abstract: Anthrax lethal toxin (LeTx) shows potent mitogenactivated protein kinase pathway inhibition and apoptosis in melanoma cells that harbor the activating V600E B-RAF mutation. LeTx is composed of two proteins, protective antigen and lethal factor. Uptake of the toxin into cells is dependent on proteolytic activation of protective antigen by the ubiquitously expressed furin or furin-like proteases. To circumvent nonspecific LeTx activation, a substrate preferably cleaved by gelatinases was substituted for the furi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…This modifed PA, designated PA-L1, is dependent upon proteolytic activation by cell surface bound MMP-2/-9. This MMP-activated LeTx is currently under development for cancer therapy (19, 20). …”
Section: Introductionmentioning
confidence: 99%
“…This modifed PA, designated PA-L1, is dependent upon proteolytic activation by cell surface bound MMP-2/-9. This MMP-activated LeTx is currently under development for cancer therapy (19, 20). …”
Section: Introductionmentioning
confidence: 99%
“…Anthrax toxin consists of three nontoxic proteins that co-assemble to produce a series of free or cell-bound toxic complexes (1). Two of the proteins, Lethal Factor (LF) 3 and Edema Factor (EF), are enzymes that modify cytosolic targets (2,3). The third, Protective Antigen (PA), is a receptor-binding and pore-forming protein that transports LF and EF to the cytosol (4).…”
mentioning
confidence: 99%
“…Previous tests of the matrix metalloprotease-activated PA (PA-L1) in combination with LF found that Colo205 was sensitive to the toxin with an EC50 of 10 ng/mL, which is 10-fold higher than the EC50 of the PA-U2/LF tested here. It was previously noted that BRAF mutational status was predictive of an in vitro response to lethal toxin treatment [48,39]. This is presumably because cells harboring the B-RAF V600E mutation depend on ERK activation for survival and growth, whereas other cell types are able to survive in the presence of ERK inhibition.…”
Section: Discussionmentioning
confidence: 99%